SP0010 Can We Change Perceptions on The Use of Glucocorticoids?. (15th July 2016) - de Wit, M.
Abstract : Glucocorticoids have a bad reputation. not only among patients but also among health professionals and the general public. It makes that the same scientific data can be interpreted differently and leads to recommendations that are seen as arbitrary. The lack of consensus confuses patients who receive different messages when prednisolon is prescribed and it hampers an effective implementation of recommendations in clinical practice. The result is that patients are not optimally informed and educated about the real benefits and risks of the treatment. It can lead to non-adherence, under-treatment, over-treatment, the use of expensive medicines and ultimately to suboptimal disease outcomes. With the new EULAR consensus document the first hurdle of controversial recommendations has been tackled. This document paves the way to a better education of patients, health professionals and general public. However, the key messages are difficult to understand and require an effort of all involved to develop an innovative approach to communicate the complex interplay between disease activity and the benefits and risks of glucocorticoid use to patients. The first step is to disseminate the recommendations in a tailored manner to the different audiences. Patients require other kinds of information and provided in other formats than health professionals or the general public. Examples will be presented during this session. Disclosure of Interest: None declared